Routine episiotomy as a cultural gender practice: other case of «female genital mutilation» - Rodrigues Ribeiro, María Augusta (Investigaciones Feministas (Feminist Research), 2020)
In the first half of the 20th century, episiotomy became a routine procedure within the technocratic paradigm of childbirth care. Studies on its effectiveness began half a century later without clear evidence of its benefits. Today, it is still widely practiced in many countries, so several authors have considered it female genital mutilation. This article aims to deepen this assertion by analyzing its practice in relation to the social construction of gender and the institution of motherhood. The analysis, developed on the basis of bibliographic research, reveals episiotomy as a gender practice constitutive of modern patriarchy, whose genesis in the 18th century is framed around the elaboration of the dispositif of sexuality theory by Foucault. In addition, the double discourse that arises from its western legitimization situates it as a disciplinary technology of colonial and gender domination.